ANALISIS GERAK DAN KARAKTER BUGIS PADA TARI HANDAGA BUGIS DI PURA MANGKUNEGARAN - Saputri, Indah Ayu (Universitas Khairun, 2023)
This study uses an ethnochoreology approach with dance ethnography methods. Judging from its culture, the multicultural art form referred to in this case is described based on the background of the movements and characters. The results of this research show Bugis movements and characters are manifested in motion motives including slulupan, ngundhing mangundha, cekotan, kiteran, geyol, ikal benang, and pencak silat. The movements and characters of Bugis ngglece are formed by the motives of the ngundhing mangundha and slulupan movements. The movement and character of the gecul are formed by the motive motion of the geyol, kiteran, and ikal benang. The motion and character of ngece is formed by the motive penthangan laku miring cekotan, and ulap tawing cekotan. The movements and characters are agile, attractive, dynamic and strong are manifested in the movements of pencak silat which have been stylized into dance movement that gives the impression of aÂ straight line, firm, and strong.Keywords: Movement and Character, Bugis, Dance